Buyer-Optimal Learning and Monopoly Pricing - Roesler, Anne-Katrin; Szentes, Balázs (American Economic Review, 2017)
This paper analyzes a bilateral trade model where the buyer's valuation for the object is uncertain and she observes only a signal about her valuation. The seller gives a take-it-or-leave-it offer to the buyer. Our goal is to characterize those signal structures which maximize the buyer's expected payoff. We identify a buyer-optimal signal structure which generates (i) efficient trade and (ii) a unit-elastic demand. Furthermore, we show that every other buyer-optimal signal structure yields the same outcome as the one we identify: in particular, the same price. (JEL D11, D42, D82, D83, L12)